Barriers to Development of Selected Municipalities of Sulu Province - Tahil, Abdurahim S.; Tahil, Shernahar K. (HM Publisher, 2021)
This study was conducted to determine the barrier to the development of selected municipalities of Sulu province. It aimed to find out the Suluanos’ concept of development in terms of political, economic, socio-cultural, technological, and ecological aspects, including how these perceived barriers affect the development of Sulu. This research utilized the descriptive method where the Quantitative aspect gathered the data from 400 adults of ten big municipalities using a checklist questionnaire. The respondents were selected through systematic sampling. For the qualitative part, the collected data were from 90 participants through focus group discussions. The statistical tools used were frequency, percentage, mean, standard deviation, and group means. The finding revealed that the Suluanos’ concept of development upheld the development policies which are participatory, equitable, appropriateness, concertizing, and environment friendly and the corresponding functions of development such as the political, economic, socio-cultural, technological, and ecological aspects. Of the five development functions, the economic aspect (2.95) was the main barrier to development. It is followed by the technological aspect (2.91), the political (2.79), and ecological (2.42) as the fourth rank. On the other hand, the socio-cultural part (2.21) was the least encountered barrier. The perceived barriers that affected the development of Sulu were related to lack of high ethical standards, transparency, accountability, effectiveness, and lack of respect for and commitment to social justice, human rights, environmental life protection, and people's empowerment. Based on the data gathered, the findings made the researcher conclude that the political, economic, technological, socio-cultural, and ecological aspects in Sulu were considered barriers to development. They were not within the bounds of good governance. Bureaucracy was weak due to the leaders' personalities, who were neither transactional nor transformational. At the same time, they were not within the context of the alternative model of development. To minimize if not eliminate the barriers to development, the government's efforts should be geared towards accountability to improve the quality of governance and dispensation of justice. Further studies are recommended to determine other predictors that can similarly evaluate the development conditions of Sulu Province.